Analysis of heat exchanger network for temperature fluctuation. (15th September 2015) - Zunlong, Jin; Wang, Dingbiao; Wei, Xinli; Wang, Yongqing
Subject to temperature disturbance, exchangers in heat exchanger network will interact. It is necessary to evaluate the degree of temperature fluctuation in the network. There is inherently linear relationship between output and inlet temperatures of heat exchanger network. Based on this, the concept of temperature-change sensitivity coefficient was put forward. Quantitative influence of temperature fluctuation in the network was carried out in order to examine transmission character of temperature fluctuation in the system. And the information was obtained for improving the design quality of heat exchanger network. Favorable results were obtained by the introduced method compared with the experimental results. These results will assist engineers to distinguish primary and secondary influencing factors, which can be used in observing and controlling influencing factors accurately.